Dose Effect of Poractant Alfa in Neonatal RDS: Analysis of Combined Data from Three Prospective Studies - Królak-Olejnik, Barbara; Hożejowski, Roman; Szczapa, Tomasz (Frontiers in Pediatrics, 2020)
Aim: To evaluate the effect of the initial dose of poractant alfa on clinical outcomes in neonatal respiratory distress syndrome (RDS) and to assess adherence to treatment guidelines recommending a dose of 200 mg/kg. Methods: Records of neonates who received poractant alfa with a less invasive technique (LISA) or with the INtubate-SURfactant-Extubate (INSURE) technique were retrieved from the aggregated datasets of three prospective RDS studies conducted between 2015 and 2019. The impact of poractant dose on neonatal outcomes was analyzed by multivariate logistic regression. The primary endpoint was the need for early (<72 h of life) mechanical ventilation (MV). Typical complications of prematurity and the need for surfactant retreatment were secondary endpoints. Deviation from the 200 mg/kg dose of surfactant was a measure of compliance with the treatment guidelines. As a complementary analysis, the rates of adverse outcomes were compared for infants receiving high (200 mg/kg ±10%) and low (100 mg/kg ±10%) doses of poractant. Results: Of 994 eligible infants, 574 received poractant alfa with LISA, and 420 received poractant with INSURE. A logistic regression model using data from all 994 infants showed that the surfactant dose had a significant effect on reducing the need for MV and retreatment; the respective odds ratios were 0.92 (95% CI: 0.90–0.95) and 0.93 (95% CI: 0.90–0.96) per 10-mg/kg dose increment of poractant alfa. This dose effect was observed across all gestational age ranges and in infants treated with LISA. In newborns treated with INSURE, the dose of surfactant only influenced the rates of retreatment (p = 0.036) but not MV (p = 0.170). No impact on other neonatal outcomes was observed. In the subset of infants who received high (N = 502) and low (N = 58) doses of poractant, the high-dose group had lower rates of MV (34 vs. 48%, p = 0.042) and lower rates of retreatment (11 vs. 21%, p = 0.045). Surfactant underdosage increased with gestational age and ranged from a minimum of −3 mg/kg in <26 weeks to a maximum of −23.5 mg/kg in >32 weeks. Conclusions: The initial dose of poractant alfa significantly impacts the need for invasive ventilation and retreatment. More mature newborns are at a greater risk of underdosing.